Viability and Vigor of Dura, Pisifera and Tenera Oil Palm (Elaeis Guineensis Jacq.) Pollen - Khin Aye Myint, NA (2010)
Selecting pollen with high viability and vigor are important for ensuring the success of oil palm seed production through controlled pollination. Therefore, an estimation of pollen viability and vigor is essential for fruit and seed setting. This study consist of three experiments. In the first experiment, pollens from three oil palm fruit-forms of 20-year old dura, pisifera and tenera palms were collected at Malaysia Palm Oil Board (MPOB) Research Station, Kluang and MPOB/UKM Research Station, Bangi. The objective of this study is to establish a favorable medium pollen germination medium for the assessment of pollen viability and vigor in three oil palm fruit-forms. Three types of media: two solid media prepared with two types of sugar i.e. 11% sucrose and glucose and another is sucrose liquid medium (sucrose 2.5%+0.01% boric acid) was investigated. Pollen was incubated at 35°C for 2 hours. Experiment was carried out by using completely randomized design with four replications. Data were collected at 60, 120 and 180 minutes. Dura pollen germination percentage as well as pollen tube growth showed good response in solid sucrose medium compared to other media. Solid sucrose media yielded highest pollen germination percentage among the media tested at 60 min (69.7%) to 180 min (75.8%) which is significantly higher than liquid medium but no difference with glucose solid medium. Liquid media gave longer pollen tube (409.0μm) but with no significant difference with solid sucrose medium (405.7μm). Only liquid medium caused the rupturing of pollen tubes. Solid glucose medium produced only shorter pollen tubes and was significantly shorter than solid sucrose and liquid sucrose medium. The effect of liquid sucrose medium was more pronounced in pisifera pollen. Solid sucrose medium emitted longer pollen tube length (372.1 μm) with smooth and slender tubes without bursting which is no difference with liquid sucrose medium (419.6 μm). At 60 min after incubation exhibited was the highest pollen germination rate (PGR) and pollen tube length rate (PTLR) was the most important counting time. For PTLR, at 60 min counting time, all media tested were not significantly different for dura pollen. Solid sucrose and liquid sucrose media had significantly higher PTLR than solid glucose in pisifera pollen. For tenera, solid sucrose and solid glucose media provided significantly higher PTLR than liquid sucrose medium. In the second experiment, the study was carried out to investigate the effect of different pollen sizes (small < 32μm and large>32μm) on pollen germinability and vigor. Experiment was carried out by using completely randomized design with four replications. Data were collected with 60 min interval up to 180 min. Results showed that small pollen generally have a higher germinability and is free from impaired factors such as slower tube growth rate and hypertrophy effect. Both rates of germination and tube growth were highest at 60 min after incubation and increase with the declining rate up to 120 min and 180 min. In the third experiment, pollen was taken from three different fruit forms of 20 and 8-year old oil palm and stored in sub-zero condition at different temperature regimes (0°C, -5°C, -10°C, -15°C and -20°C). Experiment was conducted by completely randomized design with four replications. Percentage of pollen germination (PG), rate of pollen germination (PGR), pollen tube length (PTL) and rate of pollen tube growth (PTLR) from 180 min measuring time was evaluated in each storage temperature level with 2 months interval until 6 months. Generally, all the tested pollen sources decrease viability and vigor with storage time. The germination percentage and vigor of all pollen sources were maintained during the first two months after storage. This experiment pointed that -15 °C was the best storage temperature among all the other tested temperatures regimes for both traits, pollen germination and tube growth.